Childhood behavioral inhibition and attachment: Links to generalized anxiety disorder in young adulthood - Zdebik, Magdalena A.; Pascuzzo, Katherine; Bureau, Jean-François; Moss, Ellen (Frontiers in Psychology, 2022)
Generalized anxiety disorder (GAD) is under-treated yet prevalent among young adults. Identifying early risk factors for GAD would contribute to its etiological model and identify potential targets for intervention. Insecure attachment patterns, specifically ambivalent and disorganized, have long been proposed as a childhood risk factor for GAD. Similarly, childhood behavioral inhibition has been consistently associated with anxiety disorders in adulthood, including GAD. Intolerance of uncertainty (IU), the tendency to react negatively to uncertain situations, has also been shown to be a crucial component of GAD. Furthermore, maternal anxiety is an important feature of developmental models of anxiety including GAD. Yet, to date, no study has examined, within a comprehensive model, how attachment and behavioral inhibition in childhood, maternal anxiety in adolescence and IU in emerging adulthood contribute to GAD in adulthood. The present study thus examines these links using a longitudinal design with 61 Canadian participants and their mothers. At age 6, participants’ attachment and behavioral inhibition were assessed observationally. Maternal anxiety was measured when participants were 14 years of age. IU and GAD were assessed when participants were 21 and 23 years of age, respectively. Structural equation modeling showed that IU mediates the relationships between behavioral inhibition and GAD, while controlling for maternal anxiety. Ambivalent and disorganized-controlling attachment patterns are also indirectly associated with increased GAD symptoms via greater IU scores. Furthermore, a direct and positive effect of behaviorally disorganized attachment was found on GAD symptoms. This longitudinal study supports integrating attachment, behavioral inhibition and IU in a model of GAD.